2021
DOI: 10.3390/ani11092693
|View full text |Cite
|
Sign up to set email alerts
|

Fascioliasis in Llama, Lama glama, in Andean Endemic Areas: Experimental Transmission Capacity by the High Altitude Snail Vector Galba truncatula and Epidemiological Analysis of Its Reservoir Role

Abstract: South American camelids are definitive hosts of Fasciola hepatica. However, their capacity to participate in the transmission and epidemiology of fascioliasis has never been appropriately studied. Therefore, an F. hepatica isolate from Argentine llama is for the first time analyzed using Galba truncatula lymnaeids from Bolivia. Experimental follow-up studies included egg embryogenesis, miracidial infection of lymnaeid snails, intramolluscan larval development, cercarial production, chronobiology of cercarial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…Llamas and alpacas are present in the Northern Altiplano (Figure 9(Ba)) and are known definitive hosts for F. hepatica, but a potential role as reservoirs has been ruled out, as recently proved by experimental and field studies [50]: (i) the liver fluke transmission capacity of llama isolates is not sufficiently efficient; (ii) they do not show liver fluke infection in the Altiplano because they are present in zones where dryness, absence of freshwater collections, and higher altitudes do not allow lymnaeids to be present; (iii) the dung-pile defaecation behaviour of these camelids, always far from freshwater collection, does not allow liver fluke eggs shed by these animals to reach water and infect lymnaeids [50]. Infection of alpacas has been reported from the Northern Bolivian Altiplano, but this only concerned the farm of Belen [76], which is outside the human endemic area.…”
Section: Livestock Managementmentioning
confidence: 99%
See 3 more Smart Citations
“…Llamas and alpacas are present in the Northern Altiplano (Figure 9(Ba)) and are known definitive hosts for F. hepatica, but a potential role as reservoirs has been ruled out, as recently proved by experimental and field studies [50]: (i) the liver fluke transmission capacity of llama isolates is not sufficiently efficient; (ii) they do not show liver fluke infection in the Altiplano because they are present in zones where dryness, absence of freshwater collections, and higher altitudes do not allow lymnaeids to be present; (iii) the dung-pile defaecation behaviour of these camelids, always far from freshwater collection, does not allow liver fluke eggs shed by these animals to reach water and infect lymnaeids [50]. Infection of alpacas has been reported from the Northern Bolivian Altiplano, but this only concerned the farm of Belen [76], which is outside the human endemic area.…”
Section: Livestock Managementmentioning
confidence: 99%
“…Field studies inside the human endemic area were never able to find F. hepatica infection in these camelids. Therefore, control measures for South American camelids are not needed in the Northern Altiplano [50].…”
Section: Livestock Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…This fact has encouraged the development of alternative treatment or other control strategies, such as vaccination trials, for which understanding the cross-talk interactions between hosts and parasites is of paramount importance. The study published by Mas-Coma et al [ 7 ] explored the capacity of llamas to participate in the transmission and epidemiology of fasciolosis in South America. The results showed that although eggs shed by these animals might eventually reach the adult stage, their transmission capacity should be considered negligible, and therefore, llamas should not be considered for control initiatives in fasciolosis.…”
mentioning
confidence: 99%